Correlating bacterial shedding with fecal corticosterone levels and serological responses from layer hens experimentally infected with Salmonella Typhimurium. (January 2018) - Sharma, Pardeep; Pande, Vivek; Moyle, Talia; McWhorter, Andrea; Chousalkar, Kapil
Abstract Salmonella Enteriditis andSalmonella Typhimurium are commonly isolated during egg-related outbreaks of salmonellosis and represent a significant international public health issue. In Australia, Salmonella Typhimurium is the most common serovar identified in egg product related foodborne outbreaks. While a number of studies have investigatedSalmonella shedding and host responses to infection, they have been conducted over a short time period. The present study sought to characterise bacterial shedding and host responses to infection in hens infected with onlySalmonella Typhimurium or co-infected with bothSalmonella Typhimurium andSalmonella Mbandaka over a 16 week period.Salmonella shedding was quantified using the most probable number and qPCR methods and was highly variable over the course of the experiment. On day 1, fecal corticosterone metabolites in birds infected withSalmonella Typhimurium (674.2 ± 109.3 pg/mg) were significantly higher than control (238.0 ± 12.62 pg/mg) or co-infected (175.4 ± 8.58 pg/mg) birds. The onset of lay occurred between weeks 6–8 post-infection (pi) and Fecal corticosterone metabolite (FCM) concentrations increased in both control and co-infected birds. Antibody responses to infection were monitored in both serum and yolk samples.Salmonella Typhimurium specific antibody was lower in co-infected animals than monoinfected animals. Bacterial loads in internal organs were characterised to determine persistence. Spleen, liver and caecal tonsils were positive for bacteria in both groups, indicating thatSalmonella was not cleared from the birds and internal organ colonization could serve as a reservoir for continued bacterial shedding.